Sources of Students' Anxiety in a Multidisciplinary Social Statistics Course. (October 2018) - Condron, Dennis J.; Becker, Jacob H.; Bzhetaj, Linda
To what extent, and why, do social science undergraduates experience anxiety about taking statistics courses? Despite holding assumptions of rampant statistics anxiety among students, sociologists have conducted few empirical studies of this issue. We extend the literature by analyzing data from a survey of sociology, social work, and criminal justice students enrolled in seven sections of our department's Social Statistics with Computer Applications course in the winter 2018 semester. Two thirds of respondents are anxious or very anxious about taking the course. They experience statistics anxiety primarily due to their lack of confidence in their ability to succeed in the course and their more general test-taking anxiety. This article offers a framework for instructors of social statistics courses to measure student anxiety and to address it in class in a way that aims to alleviate anxiety among the anxious while not alienating those who are comfortable in the course.